2011
DOI: 10.3174/ajnr.a2385
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Histogram Analysis Stratifies Progression-Free Survival in Newly Diagnosed Bevacizumab-Treated Glioblastoma

Abstract: BACKGROUND AND PURPOSE:Currently it is difficult to predict tumor response to anti-angiogenic therapy in individual patients. Our aim was to determine if ADC histogram analysis can stratify progression-free and overall survival in patients with newly diagnosed GBM treated "up-front" (ie, before tumor recurrence) with bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
124
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(132 citation statements)
references
References 27 publications
3
124
4
1
Order By: Relevance
“…There have been a few studies that have tried to identify IDH1 mutations using MR spectroscopy. The short-echo MRS is widely available on clinical scanners, though the false-positive rate is approximately 22% [35]. There have been other, more complex MRS techniques that have been more successful, such as Choi et al [36], who identified all patients with IDH mutations without false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies that have tried to identify IDH1 mutations using MR spectroscopy. The short-echo MRS is widely available on clinical scanners, though the false-positive rate is approximately 22% [35]. There have been other, more complex MRS techniques that have been more successful, such as Choi et al [36], who identified all patients with IDH mutations without false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…The MRI scans were interpreted by two neuroradiologists blinded to the patient outcome. We selected eight cardinal tumor‐related imaging features and dichotomized these features according to previous guidelines using the following criteria: ADC value,12, 13 peritumoral edema,14 contrast‐enhancing tumor (CET),15 necrosis,16 formation of cysts (cyst),16 noncontrast‐enhancing tumor (nCET),17 T1/Flair ratio,16 and deep white matter invasion 15. The exact dichotomy information is listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…High-risk patients were identified by ADCL Յ 1.2 m 2 / ms, whereas low-risk patients were identified by ADCL Ͼ 1.2 m 2 /ms, based on empiric thresholds identified in previous studies. 9,10,19,20 …”
Section: Adc Histogram Analysismentioning
confidence: 99%
“…These limitations have resulted in a surge of more advanced imaging biomarkers aimed at predicting response to therapy, as summarized in various review articles. 7,8 Among these new imaging biomarkers showing promise are diffusion MR imaging techniques, [9][10][11][12][13][14][15][16][17][18] including ADC histogram analysis. Previous results have shown that pretreatment ADC histogram analysis performed within the contrast-enhancing tumor regions can stratify patients with recurrent GBM into high-and low-risk groups.…”
mentioning
confidence: 99%